A Neuropsychological Test of Belief and Doubt: Damage to Ventromedial Prefrontal Cortex Increases Credulity for Misleading Advertising - Asp, Erik; Manzel, Kenneth; Koestner, Bryan; Cole, Catherine; Denburg, Natalie L.; Tranel, Daniel (Frontiers in Neuroscience, 2012)
We have proposed the False Tagging Theory as a neurobiological model of belief and doubt processes. The theory posits that the prefrontal cortex is critical for normative doubt toward properly comprehended ideas or cognitions. Such doubt is important for advantageous decisions, for example in the financial and consumer purchasing realms. Here, using a neuropsychological approach, we put the False Tagging Theory to an empirical test, hypothesizing that focal damage to the ventromedial prefrontal cortex would cause a “doubt deficit” that would result in higher credulity and purchase intention for consumer products featured in misleading advertisements. We presented 8 consumer ads to 18 patients with focal brain damage to the ventromedial prefrontal cortex, 21 patients with focal brain damage outside the prefrontal cortex, and 10 demographically similar healthy comparison participants. Patients with ventromedial prefrontal cortex damage were (1) more credulous to misleading ads; and (2) showed the highest intention to purchase the products in the misleading advertisements, relative to patients with brain damage outside the prefrontal cortex and healthy comparison participants. The pattern of findings was obtained even for ads in which the misleading bent was “corrected” by a disclaimer. The evidence is consistent with our proposal that damage to the ventromedial prefrontal cortex disrupts a “false tagging mechanism” which normally produces doubt and skepticism for cognitive representations. We suggest that the disruption increases credulity for misleading information, even when the misleading information is corrected for by a disclaimer. This mechanism could help explain poor financial decision-making when persons with ventromedial prefrontal dysfunction (e.g., caused by neurological injury or aging) are exposed to persuasive information.